Fundamentals of strength : principles, experiment, and applications of an internal state variable constitutive formulation - Follansbee, Paul S., 1950- (Hoboken, New Jersey : TMS- Wiley, 2014)
'Written in a manner that is accessible to both students and practitioners, Fundamentals of Strength discusses the basis and implementation of the Mechanical Threshold Stress (MTS) model. Author P. S. Follansbee, a recognized authority in the field, reviews topics related to mechanical testing, crystal structure, thermodynamics, dislocation motion, dislocation-obstacle interactions, hardening through dislocation accumulation, and deformation kinetics. The text includes an abundance of data and actual model correlations that support the model as well as examples of how the model has been implemented and used to understand the effects of new strengthening mechanisms'--
'The text includes an abundance of data and actual model correlations that support the model as well as examples of how the model has been implemented and used to understand the effects of new strengthening mechanisms'--
Includes index.
Keywords: Strength of materials -- Mathematical models; Strains and stresses